Meningkatkan Perkembangan Kognitif pada Anak Usia Dini Melalui Alat Permainan Edukatif - Muhammad Busyro Karim; Siti Herlinah Wifroh (PG-PAUD Trunojoyo, 2014)
The development ia a change that lasts a lifetime with increasing structure and function of the body is more complex in motion capability rough, smooth motion, speech and language, socialization and independence. Cognitive development is a process of thinking is the ability to link and consider the value of an event or events.cognitive potential is determined at conception but realized or not depends on the environment and the opportunities presented. To determine the understanding of the tools of educational games and to know how the implementation of the application of learning in improving the cognitive aspects through a simple APE developed TK Ihyausunnah Margorejo. This study is a description of using the technique of data collection by interview and observation. The subject is a child aged 2 years later the class teacher and TK A aged 3-4 years. Playing the role would make social capable children. While playing the role come to learn to share, learn to queue or turns and communicate with friends. The ability to manage emotions, including to understand the feelings of fear, upset, sad, angry and jealous. Children will learn to manage and understand those feelings.creativity and discipline, usually the child will take the rules and patterns of daily life and habits of the child or the parents even adults in the child’s immediate environment.